High snail expression predicts a poor prognosis in breast invasive ductal carcinoma patients with HER2/EGFR-positive subtypes. (June 2018) - Chang, Hui-Yu; Tseng, Yu-Kai; Chen, Yu-Chia; Shu, Chih-Wen; Lin, Miaw-I.; Liou, Huei-Han; Fu, Ting-Ying; Lin, Yun-Chung; Ger, Luo-Ping; Yeh, Ming-Hsin; Liu, Pei-Feng
Abstract: Background: High Snail expression is known as a poor prognostic factor in breast cancer. However, its prognostic impact for breast cancer with different molecular subtypes is still controversial. Methods: Snail expression was examined by immunohistochemistry in tissue microarray slides of 85 corresponding tumor-adjacent normal (CTAN) and 247 breast invasive ductal carcinoma (IDC) tissues. Multivariable Cox regression analysis was used to assess the impact of Snail expression on survival rate by different molecular subtypes of breast IDC patients. Results: The level of Snail expression in IDC tumor tissues was significantly higher than that in CTAN tissues. Moreover, high Snail expression had direct impacts on poor disease specific survival (DSS) and disease-free survival (DFS) in breast IDC patients with human epidermal growth factor receptor 2 (HER2)-positive and human epidermal growth factor receptor (EGFR)-positive statuses as well as the HER2 intrinsic subtype. Additionally, breast IDC patients with a combination of three prognostic factors, including high Snail expression and HER2-positive and EGFR-positive statuses, had much poor DSS and DFS with a statistically significant linear trend. Conclusion: High Snail expression could predict a poor prognosis for breast IDC patients with HER2/EGFR-positive subtypes. Graphical abstract: Image 1